CORRELATION OF FIB-4 AND APRI SCORE WITH FIBRO SCAN SCORE TO PREDICT FIBROSIS IN OBESE TYPE-2 DIABETIC PATIENTS. - Das, Amit Kumar; Sharma, Anuj; Labrez, Mohammad Zahid (Student's Journal of Health Research Africa, 2023)
Background: Non-invasive assessment methods to assess liver fibrosis are important tools where FibroScan or liver biopsy is not accessible. This study aims to assess the efficacy and performance of the fibrosis index based on four factors (FIB-4) and aspartate transaminase-to-platelet ratio index (APRI) to evaluate liver fibrosis against FibroScan for the stages of liver fibrosis in obese type-2 diabetic patients. Methods: This was a cross-sectional study conducted in a tertiary care center in Bihar, India, and the patients were enrolled within two years. During the study period, 80 patients with a confirmed diagnosis of type-2 diabetes mellitus were selected. Laboratory blood testing and FibroScan were performed in all patients with T2DM. APRI and FIB-4 were calculated using a standard formula involving laboratory parameters. Result: The performance of FIB-4 scores is nearly similar to APRI, with the area under the curve (AUC) 0.753, (95% CI) (0.711-0.795) (p<0.0001) for ≥ F2 fibrosis (significant fibrosis) and even better 0.851 (0.815-0.887) (p<0.0001) for the F4 fibrosis (cirrhosis) group. Both the tests are proven good to diagnose fibrosis but FIB-4 has more area under the receiver operating characteristic (AUROC) than APRI in each set, thus FIB-4 is considered better than APRI. Conclusion: APRI and FIB-4 scores showed good performance in detecting patients without liver fibrosis as compared with FibroScan. Based on this study, FibroScan can be avoided in patients examined for the diagnosis of mild fibrosis and cirrhosis in the source-constrained area. Recommendation: Based on the study findings, it is recommended that in resource-constrained areas, FibroScan may be avoided for diagnosing mild fibrosis and cirrhosis in patients with type-2 diabetes. APRI and FIB-4 scores have demonstrated good performance in detecting patients without liver fibrosis.